(untitled) (Research, Society and Development, 2023)
The aim of this study was to analyze the action of a natural extract (NP) added to diluted and refrigerated semen for different periods of time. To evaluate the antioxidant property of the extract, the chosen method was the DPPH (2,2-diphenyl-1-picrylhydrazyl). Initially, the radical was prepared, adding 0.1 mm. - 0.03943g of the DPPH reagent dissolved in 10 mL of 80% methanol, which was then partially (2.9mL) allocated in test tubes with the extract (0.1mL). The samples were then kept at rest and protected from light, and after 30 minutes and 24 hours, the initial and final absorbance measurements were performed, respectively, by means of a spectrophotometer at 515 nm. After the extraction, eight semen collections from two Braford bovines were carried out using an electro-ejaculator. The semen samples were diluted and added to the natural extract, refrigerated and analyzed by CASA (IVOS-IIR, Hamilton Thorne), in order to ascertain the toxicity and antioxidant potential on the spermatozoa, evaluating the effects of the compound on the kinetics of sperm movement and on sperm morphology. Most of the evaluated parameters did not show significant changes (p<0.05). Given the data obtained, it was concluded that the natural extract (NP) has no influence on the kinetics of sperm movement and on the sperm morphology of diluted semen, plus NP and cooled.